Improved Baited Remote Underwater Video (BRUV) for 24 h Real-Time Monitoring of Pelagic and Demersal Marine Species from the Epipelagic Zone - Alejandro Prat-Varela; Agusti Torres; Daniel Cervantes; Marc Aquino-Baleytó; Ana-Maria Abril; Eric E. G. Clua (Journal of Marine Science and Engineering, 2023)
Bait-based remote underwater video (BRUV) systems are effective devices for remotely observing fish and other marine organisms in challenging environments. The development of a long duration (24 h) surface BRUV observation surveys allowed the monitoring of scarce and elusive pelagic sharks and the direct impact on non-targeted species of longline fishing in the Western Mediterranean. Technological limitations, such as the limited storage capacity and a single surface camera, were improved by (i) adding a deep camera equipped with light (below 80 m depth) and (ii) replacing Gopros with a multi-camera video surveillance system (surface and depth) with a storage capacity of several days and access to real-time observation. Based on a deployment effort of 1884 h video data, we identified 11 blue sharks (Prionace glauca) and one bluntnose sixgill shark (Hexanchus griseus), a deep-sea species that scarcely swims at the surface. The real-time observation capability was a powerful tool for reducing logistical costs and for raising environmental awareness in educational and outreach programmes.

High live coral cover and incidence of a pink-spotted coral phenotype on remote reefs off Clipperton Island, Tropical Eastern Pacific - Claudia Pogoreutz; Eric E. G. Clua; J. J. Adolfo Tortolero-Langarica (Marine Biology, 2022)

Evidence of interactions between sharks and Indo‐Pacific humpback dolphins ( Sousa chinensis ) in the northern South China Sea - Agathe Serres; Wenzhi Lin; Eric E. G. Clua; Mingli Lin; Mingming Liu; Songhai Li (Marine Mammal Science, 2022)

The spawning migrations of an exploited Albulid in the tropical Pacific: implications for conservation and community-based management - Alexander Filous; Robert J. Lennox; Raphael Raveino; Alan M. Friedlander; Eric E. G. Clua; Steven J. Cooke; Andy J. Danylchuk (Environmental Biology of Fishes, 2020)

Population dynamics of roundjaw bonefish Albula glossodonta at a remote coralline Atoll inform community‐based management in an artisanal fishery - Alexander Filous; Robert J. Lennox; Paige Eveson; Raphael Raveino; Eric E. G. Clua; Steven J. Cooke; Andy J. Danylchuk (Fisheries Management and Ecology, 2020)
Fisheries management requires knowledge on the population dynamics of exploited stocks. To that end, the present study used a mark–recapture approach to characterise the population demographics of roundjaw bonefish Albula glossodonta (Forsskål) and their interaction with a data‐limited fishery on Anaa Atoll in the Tuamotu Archipelago of French Polynesia. Over the course of the study, 2,509 bonefish were tagged and 12.3% were recaptured. The L ∞ of bonefish was estimated at 71 cm fork length (FL) with a K of 0.17, based on changes in FL between capture events. Artisanal fish traps located in the migratory corridors of the atoll accounted for 94% of recaptures and these movements occurred during the waning moon. Fishing mortality increased as bonefish reach sexual maturity, recruiting to the trap fishery at age 4 with the onset of spawning behaviour. Bonefish abundance between ages 3 and 5 was estimated to be 29,079 individuals. This case study demonstrated the utility of mark–recapture in filling knowledge gaps that impede the management of data‐limited fisheries. Ultimately, these results supported the creation of an Educational Managed Marine Area and the resurgence of rahui (seasonal closure) to manage this fishery.

A Time-Extended (24 h) Baited Remote Underwater Video (BRUV) for Monitoring Pelagic and Nocturnal Marine Species - Agusti Torres; Ana-Maria Abril; Eric E. G. Clua (Journal of Marine Science and Engineering, 2020)
Baited remote underwater video systems (BRUVs) are efficient devices for remotely characterising the assemblage and relative density of fishes and other marine organisms. However, technological constraints (e.g., battery life and limited storage memory) typically limit deployment times to

Life‐history characteristics of an exploited bonefish Albula glossodonta population in a remote South Pacific atoll - Alexander Filous; Robert J. Lennox; Richard R. Coleman; Alan M. Friedlander; Eric E. G. Clua; Andy J. Danylchuk (Journal of Fish Biology, 2019)
Bonefishes Albula spp. are important components of subsistence fisheries and lucrative sport fishing industries throughout their circumtropical distribution. In Oceania, however, Albula spp. have historically been overexploited and there is a growing need to balance the demands of competing fishing sectors, making the description of their life history a regional priority. To this aim, we collected biological samples from Albula spp. of Anaa atoll, French Polynesia, to identify the species that compose the stock and estimate their life‐history parameters including age, growth, reproduction and natural mortality. Our results indicate that Albula glossodonta is the species of bonefish present, with a maximum age that is below the, 20 year longevity of the genus (8 years in males and 10 years in females). Differential growth patterns existed between the two sexes ( L ∞ = 58, 78 cm fork length ( L F ) and K = 0.38, 0.21 for males and females, respectively). Males attained sexual maturity at 43 cm L F ( c . 3 years) whereas females matured at 48 cm L F ( c . 4 years) and oocyte production was significantly related to body mass, with a maximum batch fecundity of 1,133,767 oocytes in a 4406 g (70 cm L F ) female. The gonado‐somatic index of harvested fishes indicated that the spawning season extends from March through September. Based on the observation of a, 20 year bonefish at the proximate Tetiaroa Atoll and several empirical models, estimates of natural mortality ranged from 0.21 to 0.68; however, an estimate of 0.21 was deemed most appropriate. This information facilitated the resurgence of a Rahui (temporary fishing closure) and community‐based management to protect A. glossodonta during a critical portion of their spawning season and in this context our results provide an important demographic baseline in evaluating the recovery of this fishery.